Um Uber para chamar de teu, Porto Alegre. As estratégias de comunicação entre o duplo desafio: midiatização da inovação e da conjuntura de risco/Covid-19 - Bertoni, Anaís Schüler (Universidade do Vale do Rio dos Sinos, 2021)
The purpose of this research is to investigate Uber’s communication strategies between the double challenge: the mediatization of innovation and the risk situation/Covid-19. Thus, our objective is to examine the circulation process of meanings from Uber's communication strategies offered during the launch of its interactional matrix A (MIA) in Porto Alegre, and the strategies of its interactional matrix B (MIB), permeated by the discourses of the Covid-19 pandemic through a mediatized case study. To this end, the research is structured in three chapters: the first comprises the theoretical-conceptual framework; a second addresses Uber as an object of study in mediatization society; and a third, deals with the nature of the mediatized case, specifically the development and analysis of each phase that constitute the investigation case. The observation of materials is organized into four phases: the first comprises Uber's landing strategies in Brazil, since 2014; the second, the communication strategies that support its arrival in the city of Porto Alegre, from 2015 ahead; the third, the challenge that Uber faces in the state of Rio Grande do Sul during the offer of innovation in mobility; and, finally, the fourth and final phase explores the reformulation of Uber's communication policies and strategies due to the risks posed by the new coronavirus pandemic crisis, starting in 2020. The main results of the investigation show that Uber deals with two different strategies due these two interactional matrices, which interpenetrate each other, generating a third interactional matrix (MIC) which, while offering innovation, offers security through grammars, contracts and operations set in motion by interactional circuits.
Keywords: Uber; Mobilidade; Inovação; Caso midiatizado; Covid-19; Mobility; Innovation; Mediatized case; ACCNPQ::Ciências Sociais Aplicadas::Comunicação